Pelatihan Manajemen Usaha dan Sertifikasi Produk Bagi UMKM Makanan untuk Meningkatkan Daya Saing - Dwi Ayu Widyanigsih; Mustika Hayati (TAKHADUM: Jurnal Penelitian & Pengabdian kepada Masyarakat, 2026)
This community service program aimed to improve the competitiveness of food-based Micro, Small, and Medium Enterprises (MSMEs) through business management training and product certification assistance in Bhakti Negara Village. The main problems faced by MSME actors included limited managerial capability, weak marketing strategies, inadequate product branding and packaging, and low awareness regarding product legality and certification. The program employed a participatory approach consisting of observation, socialization, training, mentoring, and evaluation stages. The training materials included business management, simple financial bookkeeping, digital marketing strategies, product packaging development, and procedures for halal certification and PIRT registration. The results indicated an improvement in participants’ understanding and awareness regarding the importance of professional business management, product branding, and business legality in enhancing consumer trust and market access. Furthermore, participants demonstrated increased motivation to develop more competitive and sustainable businesses. The program proves that an integrative and participatory empowerment approach can effectively strengthen the capacity and competitiveness of community-based food MSMEs.